Who's at greatest risk? Latent profiles of alcohol and cannabis use and related consequences among college students. (February 2023) - Hatch, Melissa R.; Bravo, Adrian J.; Looby, Alison; Hurlocker, Margo C.; ,
Highlights: Latent Profile Analyses can display the heterogeneity in alcohol and cannabis use Most students fell into a "light, infrequent alcohol and cannabis use" class 10 % of students comprised two high-risk use profiles (Profiles 3 & 4) Profiles 3 & 4 had higher likelihood of SAM use Profiles 2 & 4 had higher likelihood of alcohol- and cannabis-related consequences Abstract: Background: There is significant heterogeneity in alcohol and cannabis use patterns among college students, with some engaging in use patterns that heighten their risk for adverse consequences. Person-centered approaches can help identify those subgroups of students with riskier use patterns. Latent Profile Analyses (LPA) were conducted to identify subgroups based on alcohol and cannabis use frequency and quantity, to explore demographic covariates and to examine mean differences across subgroups on alcohol- and cannabis-related consequences, simultaneous use, and other substance use. Methods: Participants were 2, 423 college students ( M age  = 20.1; 72  % female) recruited from seven US universities who endorsed past-month alcohol and cannabis use and completed an online survey of substance use behaviors. Results: A four-profile solution was the best fitting model. Profile 1 represented "light, infrequent alcohol and cannabis use" (73.8 %), Profile 2 represented "heavy, infrequent alcohol and moderate, frequent cannabis use" (15.9 %), Profile 3 represented "moderate, frequent alcohol and cannabis use" (5.6 %) and Profile 4 represented "very heavy, frequent alcohol and heavy, frequent cannabis use" (4.7 %). Students who identify as male, White non-Hispanic, and/or Greek-affiliated were more likely to be in the heavy alcohol use profiles. Profiles 3 and 4 represent high-risk profiles, with both having a higher likelihood of simultaneous use, Profile 3 endorsing more cannabis consequences, and Profile 4 endorsing more alcohol consequences. Conclusion: Results suggest that heavy alcohol or heavy co-use heightens risk for serious adverse consequences.